Community Preferences of Woody Plant Species in a Heterogeneous Temperate Forest, China - Chen, Yun; Shao, Yizhen; Xi, Jingjing; Yuan, Zhiliang; Ye, Yongzhong; Wang, Ting (Frontiers in Ecology and Evolution, 2020)
Diversified community types provide different microhabitats for plant growth. However, whether the distribution of species is random distribution or ecological specialization within different plant community types remains to be elucidated. Here, five 1 ha (100 m × 100 m) plots with different communities were established in a temperate forest. We examined community structure differences by nonmetric multidimensional scaling and betadisper test, analyzed the species–community relationships by correlation network approach, and then the examined distribution preferences of woody plant species by torus-translation test. Results showed that the abundance, richness, and species composition of woody plants exhibited significant differences among the five communities. The specialization index showed that 42.83% of the species had the characteristics of distribution specialization for different communities. The torus-translation test showed that 85 species (86.74%) were positively associated with specific community. Our findings suggested that the distribution of woody plants species among different plant community types is not random but specialization. Different woody plant species have distinct specific preferences among various plant community types in temperate mountain forest. These findings provide new insights into the biodiversity conservation of woody plant species in temperate deciduous broad-leaved forests and indicate the potential importance of community partitioning for the maintenance of woody plant diversity.